방송 뉴스의 재난보도 콘텐츠에 대한 분석: 지상파 3사와 JTBC의 세월호 참사 보도를 중심으로 - 최진봉; Choi, Jinbong (한국콘텐츠학회 논문지, 16(12), 2016)
The news coverage of Sewol Ferry catastrophe has reprimanded from numbers of people because of false reports and mediamorphosis such as distorted news. Thus, the purpose of this study is to examine the news coverage of television news programs about the Sewol Ferry catastrophe. Specifically, this study was conducted to figure out problems with the disaster news reports of several broadcasting stations such as, KBS, MBC, SBS and JTBC. Furthermore, the study also explores about how they reported without following the rules of disaster news coverage and policy of disaster news coverage by content analysis. 세월호 참사보도는 오보와 왜곡 축소 보도, 그리고 언론 윤리에 어긋나는 자극적인 보도 등으로 인해 국민들로부터 많은 질책을 받은 바 있다. 따라서 본 연구는 우리나라 방송사들이 세월호 참사를 어떻게 보도 했는지 학술적인 분석을 시도해 보고, 재난보도가 지니는 의미를 조명해 보고자 했다. 연구결과, 우리나라 주류 방송사인 지상파 방송사들은 재난보도가 지켜야 하는 보도의 정확성과 객관성에 미흡함을 보였으며, 언론이 재난보도 과정에서 지양해야 하는 선정성과 오보 양산 등 재난보도의 문제점에서 벗어나지 못하고 있는 것으로 나타났다. 그러나 JTBC의 경우 주류 방송사들의 보도와 달리 재난보도 과정에서 사건 발생의 원인규명과 재발 방지를 위한 대안을 제시하고, 지속적인 사회적 이슈로 논의할 수 있는 장을 마련한 것으로 나타났다.